Pengaruh Jarak Antar Drain Hole Terhadap Penurunan Muka Air Tanah pada Lereng Tambang Terbuka Batubara - Rahmat Fadhilah; Lilik Eko Widodo; Irwan Iskandar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
The presence of groundwater on the slopes of the mine, which means that the slopes are saturated with water, will cause a decrease in slope stability. Drain hole is a method that can be applied to decrease groundwater level on a mine slope. This research was conducted to determine the effect of horizontal distance between drain holes on the mine slope on the decrease in groundwater level (groundwater drawdown). Groundwater flow simulation on the slopes of an open pit coal mine with 3 scenarios, without drain holes, 100 m horizontal space between drain holes, and 50 m horizontal space between drain holes, was carried out to answer the goal of this research. The results obtained from the simulation, the third scenario with a distance between drain holes of 50 m has the maximum result compared to the other two scenarios, which are the percentage of groundwater drawdown of 54.1% and groundwater discharge of 167.3 L/s. So it can be concluded that the denser the horizontal distance between the drain holes on the mine slope, the higher the groundwater drawdown on the slope.